AN UNUSUAL HIGH-MG GARNET-SPINEL ORTHOPYROXENITE FROM SOUTHERN INDIA: EVIDENCE FOR ULTRAHIGH-TEMPERATURE METAMORPHISM AT HIGH-PRESSURE CONDITIONS - Sajeev K.; Santosh M. (My University, 2006)
We report here a garnet-spinel orthopyroxenite in close association with an ultrahigh-temperature (UHT) granulite from the central part of the Madurai Granulite Block in southern India. The garnet-spinel orthopyroxenite is almost entirely composed of orthopyroxene, spinel and rare garnet in a granular texture. Spinels in the rock are characterized by high Mg (XMg = 0.69-0.71) with low Cr and Fe3+, consistent with compositions reported from spinels occurring within xenoliths in kimberlites and high pressure-temperature (P-T) Alpine complexes. The orthopyroxenes have high Al content (Al2 O3 up to 4.85 wt%), typical of equilibration under high P-T conditions. The P-T estimates derived for the garnet-spinel orthopyroxenite indicate temperatures of around 1000°C and pressures exceeding 17 kbar. The data indicate that UHT metamorphism in this locality traversed from above 17 kbar to 11 kbar prior to the final stage of isothermal decompression. Our study reports the highest pressures obtained by far, for extreme crustal metamorphism in southern India and elsewhere in Gondwana. The multi-stage decompression observed in the UHT rocks associated with the high P-T garnet-spinel orthopyroxenite could be correlated to extension of the crust and possibly of the lithospheric mantle and/or its delamination, with the asthenospheric mantle as the ultimate heat source, during the final stage of amalgamation of the Gondwana supercontinent. © 2006 Cambridge University Press.
Keywords: GARNET-SPINEL ORTHOPYROXENITE; P-T EVOLUTION; SOUTHERN INDIA; UHT GRANULITE